Interpersonal Communication of Coaches and Athletes' Achievement Motivation: A Descriptive Study of Athletes with Disabilities in Athletics - Geraldi Novian; Cindy Putri Nathania Chandra; Komarudin Komarudin; Alen Rismayadi; Salma Maharani Sopandi; Nayla Agustiani (Universitas Negeri Jakarta, 2026)
In the world of sports, interpersonal communication between coaches and athletes is key to influencing an athlete's performance and achievement motivation. This is especially true for athletes with disabilities, who often face unique physical and mental challenges. Therefore, the role of coaches is crucial in addressing these challenges. This study aims to explore the relationship between coaches' interpersonal communication and the achievement motivation of athletes with disabilities. A descriptive method was employed in this study, employing a correlational design. The subjects involved in this study were 40 disabled athletes (31 male and 9 female) in athletics in Bandung City, aged 18-45 years. A questionnaire on coaches' interpersonal communication and achievement motivation was used as the research instrument, administered once to the subjects via Google Form. A Pearson correlation test using SPSS version 25 was used for data analysis. The results showed a significant relationship between coaches' interpersonal communication and athletes' achievement motivation. This study concluded that coaches' interpersonal communication and athletes' achievement motivation are interconnected, particularly for athletes with disabilities, who tend to require a more involved coach role in their training. This study suggests that coaches should improve interpersonal communication to further enhance the achievement motivation of athletes with disabilities.